Antioxidant Activities of Retinoidal Benzimidazole Or Indole Derivatives in In Vitro Model Systems - Ates-Alagoz, Zeynep (Current Medicinal Chemistry, 2013)
The antioxidants and antioxidant enzyme systems belong to the major protective systems of the organism. The use of retinoic acid in many animal models of carcinogenesis has also suggested that its action may depend on its antioxidant activity. Retinoids have been shown to function as effective antioxidants by inhibiting microsomal lipid peroxidation. The importance of antioxidants for the maintenance of health and for protection from oxidative stressinduced damage places them in the forefront of mechanistic approaches to genetically originated diseases related to retinoids. It is well known that cellular and subcellular membranes are susceptible to lipid oxidation because of their relatively high concentration of polyunsaturated fatty acids and their close proximity to oxygen, transition metals and peroxidases. Therefore, there has been a great deal of interest in the study of reactive oxygen species (ROS) which are associated with arteriosclerosis, nephritis and carcinogenesis. Antioxidants scavenge and prevent the formation of free radicals so they are highly important for the treatment of these kinds of diseases. For this reason, antioxidant properties of retinoidal benzimidazole or indole derivatives have been investigated in this review.
Keywords: retinol